Rereading Rosenhan. (January 2020) - Cummins, Ian
Rosenhan's pseudopatient experiment is one of the most famous psychological studies or experiments that has ever been conducted. The experiment took place at the end of a period in the 1960s which saw the intellectual base of psychiatry and psychiatric institutions challenged. There were two parts of the experiment. The first looked at the process of the psychiatric diagnosis; the second examined the experience of patients' on the wards. Rosenhan argued that psychiatric diagnosis is not consistently reliable and it has to be viewed as situationally and culturally specific. This is the finding that is most consistently highlighted from the work. However, this article argues that the other elements to Rosenhan's challenge to institutionalized psychiatric care—that diagnosis is a label that shapes subsequent perceptions of behavior and that psychiatric institutions are depersonalizing—have often been overlooked. Given the current crisis in mental health-care provision, it is argued that this critique of institutional care needs to be revisited. There is a danger that failings in current mental health provision will lead to calls for a shift in the focus toward institutionalized provision of care. The lessons of Rosenhan can be used not only to counter this but also as a basis for a value-informed approach to the provision of institutionalized mental health care.